2021
DOI: 10.4149/bll_2020_014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of voltage‑gated potassium channels affect expressions of miR-126 and miR-126* in breast cancer cell lines

Abstract: We aimed to determine the possible correlation between voltage-gated potassium channels and micro RNAs in breast cancer and metastatic breast cancer cells. METHOD: Kv1.3 and Kv10.1 channels were inhibited by specifi c siRNAs using a lipofectamine-based transfection in MCF-7 and MDA-MB-231 cells. After transfection, total RNA was isolated, and then miR-126 and miR-126* expressions were observed using RT-PCR. RESULTS: There was a negative correlation between Kv channels and miRNAs according to the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Recently, it has been demonstrated that Kv2.1 may enhance contacts between the endoplasmic reticulum and the plasma membrane in excitable cell lines [39]. More recently, an investigation on other Kv subtypes reported the localisation of Kv1.3 in the plasma membrane, the inner mitochondrial membrane, the cis-Golgi compartment and in the nuclear membrane system [24]. In addition, Kv1.1, Kv1.2 and Kv2.2 have been found to be localised in the nuclear fraction of human brain tissue and cancer cells [22,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that Kv2.1 may enhance contacts between the endoplasmic reticulum and the plasma membrane in excitable cell lines [39]. More recently, an investigation on other Kv subtypes reported the localisation of Kv1.3 in the plasma membrane, the inner mitochondrial membrane, the cis-Golgi compartment and in the nuclear membrane system [24]. In addition, Kv1.1, Kv1.2 and Kv2.2 have been found to be localised in the nuclear fraction of human brain tissue and cancer cells [22,40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, KCNB1 polymorphisms were correlated to CRC treatment and patient's outcome in Tunisia population [19]. Kv channels are mostly expressed in the plasma membrane, and diverse Kv channels also exist in intracellular organelles [20][21][22][23][24]. Therefore, one of the major challenges is to determine whether the intracellular localisation of Kv channels might be involved in malignant transformation [12,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Kv10.1 is highly expressed in BC MCF-7 cells. The inhibition of Kv10.1 expression can up-regulate miR-126, thereby reducing the invasiveness of BC cells ( 20 ).…”
Section: Relationship Between Potassium Channel and Tumormentioning
confidence: 99%